Sensitivity and event reconstruction with the Radio Neutrino Observatory Greenland (RNO-G) - Ilse Plaisier; Christoph Welling (Zenodo, 2020)
Deployment of the Radio Neutrino Observatory Greenland (RNO-G) is planned to start in 2020 at Summit Station, Greenland. In the next few years, thirty-five stations will be deployed and RNO-G will also act as a pathfinder for IceCube-Gen2. The aim is to detect astrophysical neutrinos at energies beyond the ones thus far observed. The deep positioned trigger (100 m depth) maximizes the effective detection volume of around 1 km^3 per station at an energy of 1EeV. The spacing and positioning of the antennas and strings are optimized for neutrino energy and arrival direction reconstruction with a single station. A surface component will act as a cosmic ray veto, to reduce background. This poster will give an overview of the current state of simulations and reconstruction methods for RNO-G and will detail its expected sensitivity.